The Influence of Students’ Personality Types to Their Speaking Achievement on the Tenth Grade Students of the State Senior High School 6 Palembang - Yuspar Uzer (English Department, University of Riau Kepulauan, Batam,Indonesia, 2017)
This research discussed the influence of students’ personality types to their speaking achievement. This research used experimental method in collecting the data. The instruments utilized in the inquiry were personality questionnaire and test. The result of the questionnaire and test given to a group of students to the tenth grade students of State Senior High School 6 Palembang show that students’ personality types did not influence their speaking achievement. From the result of R-square (coefficient determination) between independent variable was 0.018. It means that personality types only give little on English speaking achievement. From the study, it shows that there might be other factors that influence speaking achievement. Although personality only gives small contribution, students with extrovert type learn best by talking and physically engaging in the environment. Talking helps their thoughts to form and become clear. Introvert students learn best through quite. Therefore, extrovert students whose personality tends to be more active are better in mastering English speaking than introvert students whose personality tends to be shy, timid and quiet.